Teaching microbial analysis techniques for the characterisation of baker's yeast through the inquiry-based laboratory - Muhammad Saefi; Widi Cahya Adi; Amining Rahmasiwi; Hidayati Maghfiroh; M. Eval Setiawan; Miza Nina Adlini; Syarif Rizalia (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Laboratory course activities often focus on "cookbook style," so their activities have not yet integrated with scientific thinking as an essential aspect. In this research, the laboratory experience of microbial analysis techniques was redesigned using alternative inquiry to involve students in isolating and characterising yeast to make the bread rise. This research aimed to determine the effect of implementing inquiry-based laboratory experiences on improving students' technical skills and the structure and characteristics of laboratory courses. The method used a single case study to obtain a complete picture regarding implementing laboratory course redesign. Laboratory experience activities consisted of pre-laboratory (reinforcement of theory) and investigation (preparation of methods, laboratory investigation activities, data analysis and presentation, and writing written reports). Overall, our results suggest that inquiry-based laboratory experiences can improve students' microbial analysis technique skills in strong collaboration. In addition, students considered several benefits from this learning, such as developing designs and conducting laboratory investigations close to the original context. With these results, educators can use the redesign of this laboratory course without applying full "course-based undergraduate research experiences" to students.